POTENSI ALGA SEBAGAI GREEN INHIBITOR KOROSI DAN TEKNO-EKONOMI ANALISIS PRODUKSI LARUTAN PICKLING MENGANDUNG INHIBITOR DARI ALGA - Hafizh Arsytari Wahyudi, - (2020)
The corrosion process either due to the environment or during the pickling process, cannot be stopped. However, the corrosion rate can be slowed down by various methods, one of which is by adding corrosion inhibiting compounds. Algae contain compounds that have free electron relations in O, P, S and N heteroatoms, aromatic cycins, conjugated bonds and π or σ bonds, so algae used as corrosion inhibitors that are environmentally friendly and relatively inexpensive. The purpose of this research was to see the method of inhibitor preparation, the content of active compounds, the potential, and the corrosion inhibition process of algae and the economic evaluation of pickling production containing inhibitors of Sargassum muticum on a factory scale. The literature review was carried out using the best evidence review model from 40 articles published by international journals in the 2009-2020 period obtained from Google Scholar, Science Direct, Research Gate, PubMed ACS Publication, Spinger, and Elsevier. By using a subject with a title related to algae as a corrosion inhibitor with the keywords green inhibitor, corrosion inhibitor, seaweed, algae and microalgae. Engineering and economic evaluation includes parameter values of GPM (Gross Profit Margin), PBP (Payback Period), and CNPV (Cumulative net present value), and BEP (Break even point) which is calculated based on mathematical calculations using the Microsoft Excel application under ideal conditions to conditions from. From the literature review, it was found that the inhibitor of algae was proven to reduce the dominant corrosion rate in the range of 43.75-100% which was prepared using the reflux method with active compounds containing amino acids, flavonoids, alkaloids, triterpenoids, saponins, tannins and phenolics. Inhibition mechanism occurs by physiorption following the Langmuir isotherm. From the economic evaluation, the results obtained reach a profit of up to 66.15%, in ideal conditions PBP can be achieved in 3.49 years and CNPV until the 20th year gives a positive value. Thus, the production of preservative solutions containing inhibitors can be a viable project, especially in maritime and industrialized countries. Analysis still needs to be done to improve production efficiency and to increase profits so that they can be more attractive to investors.